Review Of Entrepreneurial Literacy For Optimizing MSME Business Strategy In The Religious Tourism Area Of Sunan Ampel Tomb Surabaya - Huddy Iswanto; Wasis Jatmiko Aji; Sudarmiatin Sudarmiatin; Rizky Firmansyah (Pusat Riset dan Inovasi Nasional, 2024)
In this era of globalization, business challenges are increasingly complex along with technological developments and global market access. Entrepreneurial literacy is the main key in dealing with this dynamic, where a good understanding of business strategy is essential for business continuity. Religious tourism areas such as the Tomb of Sunan Ampel Surabaya have great potential as tourist destinations and centers of community economic activity. However, MSMEs in the region are faced with various challenges, such as intense competition, lack of entrepreneurial literacy, and lack of effective business strategy implementation. Ideally, MSMEs in the region should have a high level of entrepreneurial literacy and be able to optimize their business strategies to increase competitiveness and local economic contribution. This study aims to investigate business strategies that can be applied by MSMEs in the religious tourism area of Makam Sunan Ampel Surabaya, by considering entrepreneurial literacy as the main foundation. This research makes a new contribution by examining the relationship between entrepreneurial literacy and MSME business strategies in religious tourism areas, adding insight into the specific context of Sunan Ampel Tomb Surabaya. This research has high urgency because it provides a foundation for the development of MSMEs in the region, increasing their competitiveness, and at the same time supporting the development of religious tourism in Surabaya.This research use desciptive qualitative approach. The research subjects involved MSMEs. Data collection was carried out through observation, interviews and documentation. Data analysis involves data reduction, display, and inference, with triangulation used to ensure validity.The results of research, observations, and interviews show that the research emphasizes the need to improve MSME entrepreneurial literacy in the Religious Tourism Area of Sunan Ampel's Tomb. Effective training and mentorship, with more than 70% of MSMEs involved, encourages business adaptation to uncertainty. Collaboration with entrepreneurship experts and the business community plays an important role. The integration of technology and business networks supports sustainable business growth and supports local tourism. This study summarizes effective strategies to increase entrepreneurial literacy, strengthen the contribution of MSMEs, and safeguard cultural heritage.